A Comparative Evaluation of Four Different Regression Equation Based Mixed Dentition Analysis in Children and Young Adolescents of Bihar Population - Divya Jyoti; Jeevendranath Shukla; Arvind Kumar; Shalini Shalini; Swati Sagar; Saurabh Raj (Journal of Pharmacy and Bioallied Sciences)
Aim: To evaluate four regression equation-based mixed dentition analyses in a Patna population and assess their accuracy and correlation. Materials and Methods: This study analyzed 84 school children aged 11–13. Dental impressions were used to measure tooth dimensions with calipers. Measurements were compared to values from different regression equations using a paired t-test. Results: The average disparity between the real and estimated values of canines and premolars exhibited notable clinical and statistical significance (P < 0.001). Conclusion: All four regression equations were not accurately applicable to this population.